Regional Economic Outlook, November 2017, Europe : Europe Hitting Its Stride. (Regional Economic Outlook, 2017)
The European recovery is strengthening and broadening appreciably. Real GDP growth is projected at 2.4 percent in 2017, up from 1.7 percent in 2016, before easing to 2.1 percent in 2018. These are large upward revisions-0.5 and 0.2 percentage point for 2017 and 2018, respectively-relative to the April World Economic Outlook. The European recovery is spilling over to the rest of the world, contributing significantly to global growth. In a few advanced and many emerging economies, unemployment rates have returned to precrisis levels. Most emerging market European economies are now seeing robust wage growth. In many parts of Europe, however, wage growth is sluggish despite falling unemployment.